English Interference on Balinese Dialect in Tejakula Village - Jaiswara, I Komang Aris (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
There is phenomenon occured in Bali, where the people use Balinese as the first language and Indonesian & English became the second language. This study aimed to analyze the phonological interference of the Balinese dialect on English. This research had a type of qualitative research. The research methods and techniques consist of methods and techniques for providing data, data analysis methods, and data presentation methods and techniques. The data collection of this research was done by asking native speakers of Tejakula village to read some English words and the researcher recorded them. The text used by researcher was randomly and without prior notice, so that native speakers had no preparation to study it first. The method used to analyze data was the articulatory phonetic equivalent method. While the methods used to deliver the results of this study were formal and informal methods. Based on the results of the study, it was found that the phonological interference of the Balinese dialect to English. The interference was heard clearly in the hissing sound. As well as other interference that occurs in the sound /æ/ in the middle, /th/, /ʃ/, and the sound ending in sound /o/.